1 - ‘I’d rather see a sermon than hear one...’: Africa/Heaven and Women of the Diaspora in Creating Global Futures and Transformation - Niaah, Jahlani A. H. (Africa Development, 2021)
This article focuses on the case of the Rastafari, a grassroots, male-dominated pan-African religio-political movement, which for almost a century has driven the Caribbean Diaspora to dialogue and action on issues of repair and redevelopment of the continent. Though often criticized as patriarchal, since the mid-1970s the Rastafari has increasingly seen women emerging, playing a leading role in globally coordinated initiatives. Indeed, it could be argued that relative to the wider society Rastafari has made more significant advances with regard to gender parity and the advancement of women, as this is facilitated by the ongoing dialogical and grounded processes of ‘reasoning’ that provide ventilation and strategic solutions for contending ideas. Women within the Movement are therefore ironically over-represented relative to their numbers in positions of international leadership and the general administration of the community. This phenomenon has grown especially over the past two generations, as the role of the Rastafari Empress, or the lioness as she is sometime referred to, has evolved to situate itself seated among the lions as a primary component within the ‘works’ of Rastafari. The article seeks to develop a historiography of the evolution of the Rastafari family and its construction of a global politics that offers the potential for black women’s empowerment ; a point recognized by womanist-oriented females who take on leadership within the Movement.